Pengaruh Pengalaman Kerja, Pelatihan dan Promosi Jabatan Terhadap Kinerja Pegawai di Dinas Pemberdayaan Perempuan Perlindungan Anak Pengendalian Penduduk Dan Keluarga Berencana Kabupaten Dairi - Aini Pandiangan; Arfan Budiman; Julkarnaen Hasibuan; Siti Widya Wulandari; Muhammad Zuhri Pulungan; Fanny Heruna Yasseff (Journal of Trends Economics and Accounting Research, 2023)
This research aims to find out the influence jointly or partially between work experience, training and promotion to the performance of the Workers at the Dinas Pemberdayaan Perempuan, Perlindungan Anak, Pengendalian Penduduk dan Keluarga Berencana Kabupaten Dairi. This research uses descriptive qualitative method using primary and secondary data. The population is the workers of the company. Forty three workers become the sample of this research. Data analysis technique used is linear regression which shows that from the three independent variables applied to the regression model (work experience, training and promotion). Work experience is significant for 0,000 which can be concluded that work experience affects performance (hypothesis 1 accepted). Training has significant value 0,048 which can be concluded that training affects performance (hypothesis 2 accepted). Promotion variable has significant value 0,019 which means that promotion influences performance (hypothesis 3 accepted). Research results show that work experience, training and promotion all positively influence the performance of the workers. It can be proven using the result of regression statistic test with probability value 0,000 obtained which is lower than α (α=0,05). So, it can be said that work experience, training and promotion influence positively the performance of the workers. Thus, hypothesis 4 accepted.